The Brain-Nose Interface: A Potential Cerebrospinal Fluid Clearance Site in Humans - Mehta, Neel H.; Sherbansky, Jonah; Kamer, Angela R.; Carare, Roxana O.; Butler, Tracy; Rusinek, Henry; Chiang, Gloria C.; Li, Yi; Strauss, Sara; Saint-Louis, L. A.; Theise, Neil D.; Suss, Richard A.; et al. (Frontiers in Physiology, 2022)
The human brain functions at the center of a network of systems aimed at providing a structural and immunological layer of protection. The cerebrospinal Fluid (CSF) operates to maintain a physiological homeostasis that is of paramount importance to proper neurological activity. CSF is largely produced in the choroid plexus where it is continuous with the brain extracellular fluid and circulates through the ventricles. CSF movement through the central nervous system has been extensively explored. Across numerous animal species, the involvement of various drainage pathways in CSF, including arachnoid granulations, cranial nerves, perivascular pathways, and meningeal lymphatics, have been studied. Among these there is a proposed CSF clearance route spanning the olfactory nerve and exiting the brain at the cribriform plate and entering lymphatics. While this pathway has been demonstrated in multiple animal species, evidence of a similar CSF egress mechanism involving the nasal cavity in humans remains poorly understood. This review will synthesize contemporary evidence surrounding CSF clearance at the nose-brain interface, examining across species this anatomical pathway, and its possible significance to human neurodegenerative disease. Our discussion of a bidirectional nasal pathway includes examination of the immune surveillance in the olfactory region protecting the brain. Overall, we expect that an expanded discussion of the brain-nose pathway and interactions with the environment will contribute to an improved understanding of neurodegenerative and infectious diseases, and potentially to novel prevention and treatment considerations.